2017
DOI: 10.1177/2325967117712236
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Nontraumatic Shoulder Pain in a Regional Sample of Female High School Volleyball Athletes

Abstract: Background:Shoulder pain is becoming increasingly problematic in young players as volleyball gains popularity. Associations between repetitive motion and pain and overuse injury have been observed in other overhand sports (most notably baseball). Studies of adult athletes suggest that there is a shoulder pain and overuse problem present in volleyball players, but minimal research has been done to establish rates and causes in juvenile participants.Purpose:To establish rates of shoulder pain, regardless of whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
1
19
0
3
Order By: Relevance
“…Twenty‐eight articles focused on pain of the elbow and/or shoulder related to overhead sports, published between 1965 and 2017. The studies were conducted in the USA, Japan, Norway, Brazil, Taiwan, and the UK . Sixteen of the articles that reported pain as outcome were cross‐sectional studies, nine articles collected data prospectively, and two studies had a retrospective design …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐eight articles focused on pain of the elbow and/or shoulder related to overhead sports, published between 1965 and 2017. The studies were conducted in the USA, Japan, Norway, Brazil, Taiwan, and the UK . Sixteen of the articles that reported pain as outcome were cross‐sectional studies, nine articles collected data prospectively, and two studies had a retrospective design …”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐five of the 28 studies that reported pain as outcome focussed on youth baseball players . The three other studies described pain rates for handball, volleyball or handball, volleyball, and basketball . Most studies used a binary scale to evaluate the presence of elbow or shoulder.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from three studies (n = 82, n = 68 females) report 4‐8° thoracic extension occurring during arm elevation with studies reporting variable ranges and degrees of other thoracic movement. Findings are relevant to athletes engaged in overhead sporting activities where deficiencies in thoracic extension may place more stress on other components of the kinetic chain resulting in pain, altered performance, and impact on an athlete's ability to train and compete . Whilst a recent review found inconclusive evidence of a relationship between static thoracic posture and shoulder complaints, functional kinetic chains are dynamic, requiring a variable mix of movement, motor control, and strength across the component parts, including the thoracic spine to enable performance of skilled functional movement.…”
Section: Discussionmentioning
confidence: 97%
“…Findings are relevant to athletes engaged in overhead sporting activities 1,3 where deficiencies in thoracic extension may place more stress on other components of the kinetic chain resulting in pain, altered performance, and impact on an athlete's ability to train and compete. 1 Whilst a recent review found inconclusive evidence of a relationship between static thoracic posture and shoulder complaints, 15 functional kinetic chains are dynamic, requiring a variable mix of movement, motor control, and strength across the component parts, including the thoracic spine to enable performance of skilled functional Upper thoracic Crosbie et al 38 Extension 2 [1,3] Lateral flexion (Ipsilateral) 3 [2,3] Rotation (Ipsilateral) 7 [5,9] Lower thoracic Crosbie et al 38 Extension 6 [4,8] Lateral flexion (Contralateral) 3 [2,4] Rotation Rotation (Ipsilateral) 7 [5,9] Lower thoracic Crosbie et al 38 Extension 2 [1,2] Lateral flexion (Contralateral) 7 [5,8] 38 Stewart et al 37 Extension…”
Section: Unilateral Shoulder Movementmentioning
confidence: 99%
See 1 more Smart Citation